Characterization of the novel HLA‐C*01:214 allele by sequencing‐based typing. (20th May 2021) - Jacob, Valentine; Dard, Céline; Desoutter, Judith; Guillaume, Nicolas
Abstract : HLA‐C*01:214 differs from HLA‐C*01:02:01:01 by one nucleotide substitution in codon −10 in exon 1.